2017
DOI: 10.1111/wvn.12268
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Health Students’ Intention to Use Evidence‐Based Practice After Graduation: A Systematic Review of Predictive Modeling Studies

Abstract: Although using a developing method, this review presents a unique contribution to further discussions regarding students' intention to use EBP following graduation. Despite limitations, consideration of identified factors for undergraduate curriculum could support student's intention to use EBP in their respective clinical environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…Among the different predictive factors, the intention to adopt or use EBP in future practice as a clinical behavior has been identified as an important and strong predictor of the subsequent utilization of EBP . Other studies associated the following factors to increased EBP adoption among nursing students: positive attitudes and belief capabilities, adequate skills, and academic and clinical support …”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the different predictive factors, the intention to adopt or use EBP in future practice as a clinical behavior has been identified as an important and strong predictor of the subsequent utilization of EBP . Other studies associated the following factors to increased EBP adoption among nursing students: positive attitudes and belief capabilities, adequate skills, and academic and clinical support …”
Section: Literature Reviewmentioning
confidence: 99%
“…Our results expose misconceptions of EBM and SDM hidden in our sample of PowerPoint slides. Educators that design formal curricula to foster EBM and SDM skills need to address all curricular elements that may impact how students value these skills [37]. Our results suggest that PowerPoint slides may contribute to the hidden curriculum and that "day-to-day" standard didactic lectures may reflect an underlying microculture at odds with EBM and SDM frameworks.…”
Section: Discussionmentioning
confidence: 86%
“…Bandura's SCT (, ) underpinned the model, with variables determined from the theory, literature, and a systematic review (Ramis et al., ). Educational assessment categories for measuring domains of EBP (Tilson et al., ) were also considered.…”
Section: Methodsmentioning
confidence: 99%
“…Allied health professionals in another study were found to lose confidence with EBP over a 5‐year period in clinical practice (Klaic, McDermott, & Haines, ). A systematic review found EBP attitudes, capability, and support from clinical and academic environments influence students’ intention to use evidence in practice (Ramis, Chang, & Nissen, ). However, the small number of included studies ( n = 3) and heterogeneity of interventions and populations limit confidence in results.…”
Section: Introductionmentioning
confidence: 99%